Ideology and succession politics in Ethiopia: autocratic leadership turnover and political instability. Issue 8 (17th November 2021) - Opalo, Ken Ochieng'; Smith, Lahra
ABSTRACT: Recent scholarship on the institutionalization of politics in Africa has highlighted the consolidation of constitutional leadership turnover in electoral democracies. However, leadership turnover is not limited to democracies, and is increasingly also regularized in a subset of non-democratic regimes ruled by dominant parties. Why have some dominant ruling parties in Africa been able to facilitate leadership turnover while others have not? With evidence from a detailed case study of Ethiopia's leadership transitions, we argue that the historical persistence of ideology and its institutional expressions are important drivers of dominant parties' ability to manage leadership turnover. In Ethiopia, the ideology of ethno-national self-determination (forged in the 1960s) influenced political development for decades, culminating in the adoption of constitutional ethnic federalism and the creation of a ruling party alliance comprised of ethno-national parties. This institutional backdrop defined the contours of transitions in 2012 and 2018. It also explains contestations over the nature of federalism in Ethiopia, including the outbreak of conflict in Tigray in 2020. In addition to highlighting the role of ideology in African politics, this paper brings a comparative perspective to the study of Ethiopia, a country that is often studied in isolation.